ANALYSIS OF RICE PRICE INCREASE OR DECREASE IN WEST JAVA AND EAST JAVA IN 2003 USING THE LINK INDEX - Sarita Anggiaty; Hj. Latifah, SSi, MMSi Hj. Latifah, SSi, MMSi (Jurnal Sistem Informasi, 2007)
Index is one measure in the science of statistics used to indicate changes in the value of a set of variables relate to one another.  The numbers generated in a calculation by using a chain index is expressed in percent.